2018
DOI: 10.1002/jcp.27095
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA SNHG3 induces EMT and sorafenib resistance by modulating the miR‐128/CD151 pathway in hepatocellular carcinoma

Abstract: Dysregulation of long noncoding RNAs (lncRNAs) plays important roles in carcinogenesis and tumor progression, including hepatocellular carcinoma (HCC). Small nucleolar RNA host gene 3 (SNHG3) has been considered as an lncRNA to be associated with a poor prognosis in patients with HCC. Here, we reported that SNHG3 expression was significantly higher in the highly metastatic HCC (HCCLM3) cells compared with the lowly metastatic HCC cells (Hep3B and PLC/PRF/5). Furthermore, forced expression of SNHG3 promoted cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
139
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(143 citation statements)
references
References 21 publications
3
139
0
1
Order By: Relevance
“…SNHG3 was firstly implicated in Alzheimer's disease (AD) and its upregulation might be an indicator of a wider dysregulation of translational machinery and ribosome biogenesis during AD neurodegeneration [11]. Subsequently, it was revealed to be an oncogene and a biomarker of malignant status or poor prognosis in several types of cancers, including colorectal cancer, ovarian cancer and hepatocellular carcinoma [12][13][14]. However, no studies to date reported its potential tumor suppressor function in cancer.…”
Section: Introductionmentioning
confidence: 99%
“…SNHG3 was firstly implicated in Alzheimer's disease (AD) and its upregulation might be an indicator of a wider dysregulation of translational machinery and ribosome biogenesis during AD neurodegeneration [11]. Subsequently, it was revealed to be an oncogene and a biomarker of malignant status or poor prognosis in several types of cancers, including colorectal cancer, ovarian cancer and hepatocellular carcinoma [12][13][14]. However, no studies to date reported its potential tumor suppressor function in cancer.…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs are most frequently studied and some of them have been proved to be significantly dysregulated in HCC, promoting tumor progression and sorafenib resistance [83,84]. Consistent with the idea that certain cell states determine drug sensitivity, miRNAs, as well as other ncRNAs including lncRNAs that mostly act as sponges of miRNAs, modulated sorafenib sensitivity through regulating EMT and stemness in HCC [85]. There are no studies reporting the role of circular RNAs (circRNAs) in sorafenib resistance yet, however, circRNA was involved in regulating stemness features of HCC cells [86].…”
Section: Post-transcriptional Regulationmentioning
confidence: 84%
“…So far, lots of lncRNAs have been con rmed to be involved in EMT. For example, lncTCF7 and SNHG3 can promote the progress of cancer through enhancing EMT in HCC 19,20 .…”
Section: Discussionmentioning
confidence: 99%